2020
DOI: 10.3389/fonc.2020.00536
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Rare Tumors: Routes to Targeted Therapies

Abstract: Comprehensive Genomic Profiling may be informative for novel treatment strategies and to improve outcomes for patients with rare tumors. This study aims to discover opportunities for use of targeted therapies already approved for routine use in patients with rare tumors. Solid tumors with an incidence lower than 2.5/100,000 per year was defined as rare tumors in China after comprehensive analysis based on epidemiological data and current availability of standardized treatment. Genomic data of rare tumors from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…According to the definition and update of rare tumors published/established by the China National Cancer Center ( 3 ), we collected and retrospectively analyzed data on immunotherapy-related indicators from a total of 852 rare tumors patients in the Geneplus database, including 136 reports of PD-L1 expression, 821 reports of TMB, 705 of MSI and 355 of HLA-I heterozygosity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the definition and update of rare tumors published/established by the China National Cancer Center ( 3 ), we collected and retrospectively analyzed data on immunotherapy-related indicators from a total of 852 rare tumors patients in the Geneplus database, including 136 reports of PD-L1 expression, 821 reports of TMB, 705 of MSI and 355 of HLA-I heterozygosity.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the incidence of therapeutic targets in rare tumors in the Chinese population was significantly higher than in the general population (53.43% vs. 20.40% respectively). Moreover, in the Chinese population, prevalence of targetable genomic alterations within those rare tumors (ALK, BRAF, BRCA2, CDKN2A, EGFR, HER2, KIT, MET, ROS1) was 32.4%, which is more than 3 times that which is found in the general population according to cBioPortal ( 3 ).…”
Section: Introductionmentioning
confidence: 91%
“…The incidence of actionable gene alterations covered by the current protocol was 32.4% among the 63 pathological subtypes, which suggests that studying these mutations in rare tumours in the Chinese patient population might help greatly improve patient outcomes. 4 Limited exploration of targeted therapy of rare solid tumours with promising efficacy Of the 133 s pathological subtypes of rare solid tumours, clinical investigations of targeted therapy cover only 11.9% (16/135) of rare solid tumours (except for all solid tumours similar to MSI-H/dMMR approved for treatment with pembrolizumab). However, notably, the ORR and disease control rate (DCR) of targeted therapy are superior to those of standard treatment in rare tumours with actionable alterations.…”
Section: High Incidence Of Actionable Gene Alterations In Rare Tumoursmentioning
confidence: 99%
“…Rearrangements include EML4-ALK translocation in non-small cell lung cancer, which can be targeted by drugs such as crizotinib. Now there is testing for biomarkers related to PD-L1 expression in various tumours that can be targeted by checkpoint inhibitors such as atezolizumab.Molecular profiling that allows matching treatments for cancers to their targets has resulted in a boost for new drug development in rare cancers by using drugs targeted to molecular biomarkers that they have in common with more common cancers, in basket trials 15. Limitations of gene expression profiling and IHC can be illustrated in diffuse large B-cell lymphoma (DLBCL) as summarized by Ofori et al in this issue of the Journal 16.…”
mentioning
confidence: 99%
“…Molecular profiling that allows matching treatments for cancers to their targets has resulted in a boost for new drug development in rare cancers by using drugs targeted to molecular biomarkers that they have in common with more common cancers, in basket trials 15 …”
mentioning
confidence: 99%